STUDENTS DIFFICULTIES IN PRONOUNCING VOWELS AT GRADE VIII MTs.S NU BATAHAN - Resdila Pratiwi (Institut Agama Islam Negeri (IAIN) Bone, 2022)
This research was to find out students’ difficulties in pronouncing vowels, particularly, in singing Maher Zain song entitled “I believe”. In order to achieve the objectives, this research was conducted through qualitative study with case study design. The subject of this research was the eight-grade students of MTs.S NU Batahan in academic year 2021/2022 that consists of 90 students. The subjects were obtained through purposive sampling. The data of students’ difficulties in pronouncing vowels as well as the reason were attained through pronunciation test, interview and observation. Based on the result of observation, interview, and test, it was found that: 1) the difficulties that faced by students in pronouncing vowel are lack of ability in pronouncing diphthongs [iə] [eə][uə][ei][ᴅi][oi] [əu] [ᴅu]. the students often pronounce consonant “r” clearly instead of long vowels [ə:],[ᴅ:] [ɔ:]. They found it difficult to pronoun the word that consist of double consonant.